2003
DOI: 10.1111/j.1933-1592.2003.tb00293.x
|View full text |Cite
|
Sign up to set email alerts
|

Indoctrination, Coercion and Freedom of Will

Abstract: Manipulation by another person often undermines freedom. To explain this, a distinction is drawn between two forms of manipulation: indoctrination is defined as causing another person to respond to reasons in a pattern that serves the manipulator's ends; coercion as supplying another person with reasons that, given the pattern in which he responds to reasons, lead him to act in ways that serve the manipulator's ends. It is argued that both forms of manipulation undermine freedom because manipulators track the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…In the domain of freedom and force, for example, we turned to existing philosophical accounts according to which an agent only performed an action freely if he or she had the possibility of behaving otherwise (Carr, 1988;Yaffe, 2003). Based on these accounts, we suggested that people's judgments about whether an agent freely performs some action depend in part on how they think about alternative possibilities in which the agent does not perform this action.…”
Section: Discussionmentioning
confidence: 97%
“…In the domain of freedom and force, for example, we turned to existing philosophical accounts according to which an agent only performed an action freely if he or she had the possibility of behaving otherwise (Carr, 1988;Yaffe, 2003). Based on these accounts, we suggested that people's judgments about whether an agent freely performs some action depend in part on how they think about alternative possibilities in which the agent does not perform this action.…”
Section: Discussionmentioning
confidence: 97%
“…If a confident agent is the product of brainwashing or indoctrination, she may not be free, but it will not be because she is a confident agent, it will be because she has been subject to an autonomy-undermining process (though explaining why such processes are autonomy-undermining is notoriously difficult. For a compelling recent attempt, see Yaffe, 2003). EDDY NAHMIAS 47 This sort of predictability is DostoyevskyÕs worry in ÔThe Underground ManÕ (see note 2).…”
Section: Resultsmentioning
confidence: 96%
“…Following this tack, we require a principle that blocks the pre‐ordination of SFA outcomes by manipulators. One serious proposal is provided by Yaffe () who argues persuasively that manipulators impede freedom in a more thoroughgoing way than brute deterministic causes insofar as manipulators track the states of their victims in nearby possible worlds and insure compliance in those worlds in a way brute forces do not. Yaffe in effect argues that because of this point, victims of manipulation lack the modal ability to do otherwise that is possessed by agents who are just the product of deterministic forces.…”
Section: More Manipulation Casesmentioning
confidence: 99%